Surface interface modified lithium-rich manganese-based positive electrode material and lithium ion secondary battery
By applying a functional material layer on the surface of the lithium-rich manganese-based positive electrode material, reversible electrochemical deintercalation of oxygen is solved, and the problem of oxidation and precipitation of materials at high voltage is significantly improved, and the cycle stability and thermal stability are significantly improved.
Patent Information
- Application Number
- CN202411663908.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The lattice oxygen activity of lithium-rich manganese-based positive electrode material in a high voltage operating environment leads to oxidation and precipitation, resulting in deterioration of cycle stability and thermal stability, making it difficult to effectively suppress it.
By applying a functional material layer on the surface of the lithium-rich manganese-based positive electrode material, the functional material can achieve reversible electrochemical deintercalation/embedding of oxygen at different potentials, inhibit oxidation and precipitation, and ensure the reversible utilization of reactive oxygen.
It significantly improves the cyclic stability and thermal stability of the material in high temperature and high voltage environments, and avoids side reactions caused by the formation of reactive oxygen species and oxygen dissipation.
Smart Images

Figure CN119481005A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion secondary batteries, and in particular relates to a surface-modified lithium-manganese-rich positive electrode material and a lithium ion secondary battery. Background Art
[0002] Lithium-rich manganese-based cathode materials are considered to be one of the key cathode materials for the next generation of lithium-ion batteries due to their high energy density and low cost. It is well known that lithium-rich manganese-based cathodes can output up to 250-400 mAh / g specific capacity when charged to 4.8V or higher, making them one of the highest known specific capacity lithium-ion battery cathode materials. However, due to the many defects of lithium-rich manganese-based cathode materials, such as low coulombic efficiency, poor rate performance, poor cycle stability, and cycle median voltage decay, there are still severe challenges in promoting market applications.
[0003] The above problems are closely related to the lattice oxygen activity of lithium-rich manganese-based cathode materials under high voltage operating conditions. Due to the oxidation migration and loss of lattice oxygen, metal ions in the transition layer migrate and serious electrolyte oxidation side reactions occur at the surface interface to produce gas. To solve the above problems, researchers use various methods to modify the materials, such as transition metal component regulation, synthesis process regulation, element doping, surface coating, and surface chemical treatment.
[0004] However, it should be pointed out that although coating has been proven to have a certain effect in inhibiting electrolyte corrosion of electrode interface and deteriorating surface interface structure, when the material is charged to high voltage or high lithium de-ion state, the lattice oxygen of the layered material will oxidize and precipitate, and it is difficult to effectively inhibit it through general coating materials. Most coating materials only consider physical isolation between electrolyte and high voltage positive electrode under the conditions of ensuring appropriate electronic conductivity and lithium ion diffusion channel. More importantly, the activity of lattice oxygen in lithium-rich manganese-based positive electrode materials is crucial to the release of high capacity of materials. If the reversible electrochemical de-insertion / embedding of oxygen can be controlled at different potentials between the coating material and the lithium-rich manganese-based positive electrode material, it can reduce the loss of oxygen and ensure the reversible utilization of active oxygen. At the same time, it can avoid the formation of oxygen from active oxygen escaping to the interface and reacting with the electrolyte, resulting in significant degradation of the cycle stability and thermal stability of the battery system.
[0005] Therefore, providing a positive electrode material that can achieve controllable reversible electrochemical oxygen extraction / insertion at different potentials between the coating material and the lithium-rich manganese-based positive electrode material has become a problem to be solved. Summary of the invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide a surface-modified lithium-manganese-rich based positive electrode material and a lithium-ion secondary battery. In the surface-modified lithium-manganese-rich based positive electrode material provided by the present invention, the application of surface functional materials inhibits the oxidation and precipitation of lattice oxygen in the lithium-rich manganese-rich based positive electrode material under high voltage delithiation, thereby significantly improving the cycle stability and thermal stability of the material under high temperature and high voltage environment.
[0007] The present invention provides a surface-modified lithium-rich manganese-based positive electrode material, comprising a lithium-rich manganese-based positive electrode material core and a functional material layer coated on the surface of the lithium-rich manganese-based positive electrode material core. The general chemical formula of the functional material is shown in chemical formula (1):
[0008] R' a R” b M c A' d A” e Chemical formula (1)
[0009] In the chemical formula (1), R' is one or more of alkali metal or alkaline earth metal Li, Na, K, Rb, Cs, Mg, Ca, Sr and Ba;
[0010] R" is one or more of the lanthanide rare earth elements La, Ce, Pr, Nd, Po, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc, and Y;
[0011] M is one or more of the transition metal elements Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Cd and Ta that can change into multiple valence states;
[0012] A' is O;
[0013] A" is one or more of S, Se, Te, F, Cl, Br and I;
[0014] The valence of the M element in the functional material includes a non-highest valence state of the M element, and / or, in a battery with metallic lithium as a negative electrode, a redox peak exists in a cyclic voltammetry curve in the potential range of 2.0-5.0V;
[0015] Ions M with a valence of +w in element M W With +(w+1) ion M w+1 The amount ratio of the substance satisfies the relationship of formula 1:
[0016] C M w :C M w+1 =(1-(VU)×a): (n-1+(VU)×a) (Formula 1)
[0017] Multivalent ions of element M with mixed valence (V hybrid ) satisfies the relationship in formula 2:
[0018] V hybrid =W+1+(V×aU×a-1) / n (Formula 2)
[0019] In formula 1 and formula 2, C M w , C M w+1 M W With M w+1 The proportion of the amount of a substance;
[0020] U is the valence of the element R'; V is the valence of the element R"; W is the valence of the element M; n is the stoichiometric ratio of the elements in the chemical formula (1); U, V, W and n are all positive integers greater than zero;
[0021] a is the content of R' element, and its value interval satisfies the relationship of formula 3:
[0022] 0≤a≤1 / 2 (V -U-1) (Formula 3)
[0023] In formula 3, a is the content of R' element, U is the valence of R' element; V is the valence of R' element; U and V are positive integers greater than zero;
[0024] The theoretical electrochemically controllable maximum oxygen removal / intercalation content in the functional material lattice satisfies the relationship of formula 4:
[0025] O intercal. = (1-V×a+U×a)×c / (2×n) (Formula 4)
[0026] Where O intercal. is the theoretical electrochemically controllable maximum oxygen removal / embedding content in the functional material lattice, U is the valence of the R' element; V is the valence of the R" element; n is the stoichiometric ratio of the elements in the chemical formula (1), U, V, and n are positive integers greater than zero; a is the R' element content, and its assignment interval satisfies the relationship of formula 3;
[0027] Assuming that the valences of R', R", M, A' and A" are U, V, W, X and Y respectively, the general chemical formula R' a R” b M c A' d A” e In the equation, a, b, c, d and e satisfy the relationship between equations 5 and 6:
[0028] a×U+b×V+c×W=d×Y+e×Z (Formula 5)
[0029] (a+b): c: (d+e)= (n+1): n: (3 n+1) (Formula 6)
[0030] In Formula 5 and Formula 6, U, V, W, X, Y and n are positive integers greater than zero; a, b, c, d and e are rational real numbers greater than or equal to zero, including decimals.
[0031] Preferably, when the functional material is assembled into a battery with metallic lithium as the negative electrode, when charged to above 4.0V, the Raman spectrum has a peak at 174cm -1 With 380cm -1 The peak intensity at the position is weakened or eliminated.
[0032] Preferably, the functional material is assembled into a battery with metallic lithium as the negative electrode for charge and discharge, and an oxidation characteristic peak above 4.40V exists on the voltage capacity differential curve dQ / dV or the cyclic voltammetry curve;
[0033] Alternatively, after the functional material is used to form a battery in an alkaline aqueous solution with a reversible hydrogen electrode (RHE) as a reference electrode, a redox characteristic peak exists in the voltage capacity differential curve dQ / dV or the cyclic voltammetry curve within the 1.2-2.0V range.
[0034] Preferably, the functional material is assembled into a battery with metallic lithium as the negative electrode for charge and discharge, and the voltage capacity differential curve dQ / dV or the cyclic voltammetry curve has a lithium extraction / insertion redox peak in the range of 0.001V-3.0V;
[0035] And / or, the functional material is assembled into a battery with metallic lithium as the negative electrode, and the lithium ion diffusion coefficient measured by variable scan rate cyclic voltammetry is higher than 10 -13 cm 2 / s.
[0036] Preferably, after the functional material is pressed into a powder cake with a diameter of 13 mm by a stress of 10 MPa, the electronic conductivity of the powder cake obtained by a four-probe test is higher than 10 mS / cm.
[0037] Preferably, the surface modified lithium-rich manganese-based positive electrode material is assembled into a battery with metallic lithium as the negative electrode, and the first cycle is charged and discharged in the range of 2.0-4.8V. X-ray photoelectron spectroscopy (XPS) is performed on the surface of the positive electrode O, F and P, O1s 531.2eV ROLi organic peak, F1s 685.0eV LiF peak and P2p 136.4eV Li x PO y F z The peak intensity is lower than the peak intensity of the unmodified lithium-rich manganese-based cathode material at the surface interface;
[0038] And / or, the surface-modified lithium-rich manganese-based positive electrode material is assembled into a battery with metallic lithium as the negative electrode, and the oxygen content detected by differential electrochemical mass spectrometry (DEMS) is less than 100umol / mg during the first cycle of charging and discharging in the range of 2.0-4.8V.
[0039] Preferably, the core of the lithium-rich manganese-based positive electrode material has a general chemical formula of Li 1+x Mn y Ni z Co m O2, where 1+x+y+z+m=2, 0≤x≤2, 0<y≤1, 0≤z, m≤1.
[0040] The present invention also provides a method for preparing the above-mentioned lithium-rich manganese-based positive electrode material, comprising the following steps:
[0041] S1: mixing a lithium-rich manganese-based precursor with a lithium source, and sintering once to obtain a lithium-rich manganese-based positive electrode material core;
[0042] S2: mixing the nanoparticle slurry of the functional material with the lithium-rich manganese-based positive electrode material core and drying the mixture to obtain a powder;
[0043] S3: performing secondary sintering at high temperature on the powder to obtain the surface-interface modified lithium-rich manganese-based positive electrode material.
[0044] The present invention also provides a lithium-ion secondary battery, comprising the above-mentioned surface-interface modified lithium-rich manganese-based positive electrode material.
[0045] Compared with the prior art, the present invention provides a surface-modified lithium-rich manganese-based positive electrode material and a lithium-ion secondary battery. The present invention utilizes the functional material to charge to a high voltage, and under the potential drive, the active oxygen species, such as O2, O2 - , O - and oxygen polymer O n- The active oxygen is absorbed and embedded into the lattice gap, and then released when discharged to a low potential, so that it returns to the lithium-rich manganese-based positive electrode material again, forming a reversible closed loop for active oxygen utilization. In the surface-modified lithium-rich manganese-based positive electrode material provided by the present invention, the application of surface functional materials inhibits the oxidation and precipitation of lithium-free lattice oxygen in the lithium-rich manganese-based positive electrode material at high voltage. The positive electrode material can be reversibly electrochemically de- / embedded with oxygen at different potentials, which significantly improves the cycle stability and thermal stability of the material in a high temperature and high voltage environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 Schematic diagram of electrochemical oxygen desorption / intercalation and lithium ion transmission between functional materials and lithium-rich manganese-based cathode materials during charging;
[0047] Figure 2The functional material composition of Examples 1-4 is lithium metal as the negative electrode (vs. Li + / Li) after the battery charge and discharge curve;
[0048] Figure 3 The functional material composition of Examples 1-4 is lithium metal as the negative electrode (vs. Li + / Li) in the range of 2.0V-5.0V;
[0049] Figure 4 The cyclic voltammetry curve of the functional material composition of Example 4 in the range of 1.2V-2.0V with a reversible hydrogen electrode (RHE) as the reference electrode;
[0050] Figure 5 The functional material composition of Examples 1-4 is lithium metal as the negative electrode (vs. Li + / Li) in the range of 0.001V-3.0V;
[0051] Figure 6 Example 4: Functional material with metallic lithium as negative electrode (vs. Li + / Li) batteries were charged to different voltages, and the Raman spectra of the functional materials obtained after disassembly;
[0052] Figure 7 The functional materials of Example 1-4 were pressed into a powder with a diameter of 13 mm by 10 MPa stress, and the electronic conductivity of the powder was tested by four-probe test;
[0053] Figure 8 The SEM images of the functional materials of Examples 1-4 are as follows;
[0054] Fig. 9 XPS graphs of the lithium-rich manganese-based positive electrode materials of Example 6 and Comparative Example 1 at different voltages during the charge and discharge process;
[0055] Fig.10 The graph of the gas composition changes detected by DEMS during the charging and discharging process of the lithium-rich manganese-based positive electrode material of Example 6 and Comparative Example 1;
[0056] Fig.11 DSC curves of the positive electrode powder and the electrolyte after the surface interface modified lithium-rich manganese-based positive electrode materials of Example 6 and Comparative Example 1 were charged to 4.8V;
[0057] Fig.12 The graph of the capacity retention rate of the lithium-rich manganese-based positive electrode material at 45°C 2.0V-4.8V of Example 6 and Comparative Example 1;
[0058] Fig.13This is a graph showing the specific capacity retention rate of the lithium-rich manganese-based positive electrode materials of Example 6 and Comparative Example 1 at different rates of 2.0V-4.8V. DETAILED DESCRIPTION
[0059] The present invention provides a functional material having electronic conductivity, electrochemically controllable oxygen ion extraction / embedding and lithium ion electrochemical activity, including element composition, chemical formula characteristics, element valence characteristics and oxygen extraction / embedding functional characteristics.
[0060] Wherein, the general chemical formula of the functional material is:
[0061] R' a R” b M c A' d A” e Chemical formula (1)
[0062] In the chemical formula (1), R' is one or more of alkali metals or alkaline earth metals Li, Na, K, Rb, Cs, Mg, Ca, Sr and Ba;
[0063] R" is one or more of the lanthanide rare earth elements La, Ce, Pr, Nd, Po, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc, and Y;
[0064] M is one or more of the transition metal elements Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Cd and Ta that can change into multiple valence states;
[0065] A' is O;
[0066] A" is one or more of S, Se, Te, F, Cl, Br and I.
[0067] Preferably, R' is selected from one or more of Li, Na, K, Ca, Sr and Ba;
[0068] Preferably, R" is selected from one or more of the lanthanide rare earth elements La, Ce, Pr, Nd, Sc, and Y;
[0069] Preferably, M is one or more of transition metal elements Ti, V, Cr, Mn, Fe, Co, Ni, and Cu;
[0070] Preferably, A" is one or more of S, Se, Te and F;
[0071] Assuming that the valences of R', R", M, A' and A" are U, V, W, X and Y respectively, the general chemical formula R' a R” b Mc A' d A” e In the equation, a, b, c, d and e satisfy the relationship between equations 5 and 6:
[0072] a×U+b×V+c×W=d×Y+e×Z (Formula 5)
[0073] (a+b): c: (d+e)= (n+1): n: (3n+1) (Formula 6)
[0074] Wherein, U, V, W, X, Y and n are positive integers greater than zero; a, b, c, d and e are rational real numbers greater than or equal to zero, including decimals.
[0075] When n=1, the chemical formula is (R' a’ R” b’ )2M(A' d’ A” e’ )4, where a'+b'=1, d'+e'=1;
[0076] When n=2, the chemical formula is (R' a’ R” b’ )3M2(A' d’ A” e’ )7, where a'+b'=1, d'+e'=1;
[0077] When n=3, the chemical formula is (R' a’ R” b’ )4M3(A' d’ A” e’ ) 10 , where a'+b'=1, d'+e'=1;
[0078] When n=100, the chemical formula is (R' a’ R” b’ ) 101 M 100 (A' d’ A” e’ ) 301 , where a'+b'=1, d'+e'=1;
[0079] According to the chemical formula and preferred elements, the following is only an example and not a limitation. The functional material can be Pr2CuO4, Pr3Cu2O7, Pr4Cu3O 10 , Pr 101 Cu 100 O 301 , Pr2NiO4, Pr3Ni2O7, Pr4Ni3O 10 , Pr 101 Ni 100O 301 , Pr2FeO4, Pr2CoO4, Pr2MnO4, Sm2NiO4, Sc2NiO4, Y2NiO4, Nd2NiO4, Nd3Ni2O7, Nd4Ni3O 10 、Nd 101 Ni 100 O 301 , Sr 0.1 Pr 1.8 CuO4、Sr 0.2 Pr 2.8 Cu2O7、Sr 0.5 Pr 1.5 CuO4、Sr 0.4 Pr 3.6 Cu3O 10 、SrPr 99 Cu 100 O 301 , Li 0.1 Pr 1.8 CuO4、Li 0.2 Pr 2.8 Cu2O7、Li 0.2 Pr 1.8 CuO4、Li 0.4 Pr 3.6 Cu3O 10 , Li 0.2 Pr 1.8 Cu 0.5 Fe 0.5 O4、Li 0.2 Pr 1.8 Cu 0.5 Mn 0.5 O4、Li 0.5 Pr 100.5 Cu 100 O 301 , Li 0.2 Pr 1.8 Cu 0.33 Fe 0.33 -Mn 0.34 O4、Li 0.2 Pr 1.6 Ce 0.2 One or more of CuO4.
[0080] In the general chemical formula, the R' content and the value of n will affect the valence state of the M element. Changes in its content can cause the M element to form a mixed state of multivalent ions. At the same time, the content of electrochemically controllable oxygen removal / embedding in the functional material lattice is controlled by the mixed valence of the multivalent ions of the M element.
[0081] The valence of the M element in the functional material includes a non-highest valence state of the M element, and / or, when a battery with metal lithium as a negative electrode is charged and discharged, a redox peak exists in the cyclic voltammetry curve in the potential range of 2.0-5.0V;
[0082] Ions M with a valence of +w in element M W With +(w+1) ion M w+1 The molar ratio satisfies the relationship of formula 1:
[0083] C M w :C M w+1 = (1-(VU)×a): (n-1+(VU)×a) (Formula 1)
[0084] Multivalent ions of element M with mixed valence (V hybrid ) satisfies the relationship in formula 2:
[0085] V hybrid = W+1+(V×aU×a-1) / n (Formula 2)
[0086] In formula 1 and formula 2, C M w , C M w+1 M W With M w+1 The proportion of the amount of a substance;
[0087] U is the valence of the element R'; V is the valence of the element R"; W is the valence of the element M; n is the stoichiometric ratio of the elements in the chemical formula (1); U, V, W and n are all positive integers greater than zero;
[0088] a is the content of R' element, and its value interval satisfies the relationship of formula 3:
[0089] 0 ≤ a ≤ 1 / 2 (V -U-1) (Formula 3)
[0090] In formula 3, a is the content of R' element, U is the valence of R' element; V is the valence of R' element; U and V are positive integers greater than zero;
[0091] The theoretical electrochemically controllable maximum oxygen removal / intercalation content in the functional material lattice satisfies the relationship of formula 4:
[0092] O intercal. = (1-V×a+U×a)×c / (2×n) (Formula 4)
[0093] In the formula, O intercal.is the theoretical electrochemically controllable maximum oxygen removal / embedding content in the functional material lattice, U is the valence of the R' element; V is the valence of the R" element; n is the stoichiometric ratio of the elements in the chemical formula (1), U, V, and n are positive integers greater than zero; a is the R' element content, and its assignment interval satisfies the relationship of formula 3.
[0094] The following will introduce the contents of Formulas 1 to 4 by way of example only, which should not be construed as limiting examples.
[0095] Taking n=1, Pr2NiO4 as an example, U=0, V=3, a=0, b=2, c=1, (d+e)=4, then Ni(M) is a mixed valence ion, C M w :C M w+1 =(1-(VU)×a):(n-1+(VU)×a) is:
[0096] C Ni 2+ :C Ni 3+ =(1-(3-0)×0):(1-1+(3-0)×0)=1:0
[0097] Ni element multivalent ion mixed valence state (V hybrid )for:
[0098] V hybrid =W+1+(V×aU×a-1) / n=2+1+(3×0-0×0-1) / 1=2
[0099] The theoretical electrochemically controllable maximum oxygen removal / intercalation content in the functional material lattice is:
[0100] O intercal. =(1-V×a+U×a)×c / (2×n)=(1-3×0+0×0)×1 / (2×1)=0.5
[0101] For further example, introducing A'=Li, the chemical formula is Li a Pr b NiO4, at this time U=1, V=3, a+b=2, the specific range needs to be determined according to the limited range of a; c=1, first calculate the formula 0≤a≤1 / 2 (V-U-1) Calculate the value range of a:
[0102] 0≤a≤1 / 2 (3-1-1)
[0103] That is, 0≤a≤0.5.
[0104] Take a = 0.2, then the chemical formula of the functional material is Li 0.2 Pr1.8 The proportion of mixed valence ions in NiO4 and Ni(M) M w :C M w+1 =(1-(VU)×a):(n-1+(VU)×a) is:
[0105] C Ni 2+ :C Ni 3+ =(1-(3-1)×0.2):(1-1+(3-1)×0.2)=0.6:0.4
[0106] Ni element multivalent ion mixed valence state (V hybrid )for:
[0107] V hybrid =W+1+(V×aU×a-1) / n=2+1+(3×0.2-1×0.2-1) / 1=2.4
[0108] The theoretical electrochemically controllable maximum oxygen removal / intercalation content in the functional material lattice is:
[0109] O intercal. =(1-V×a+U×a)·c / (2×n)=(1-3×0.2+1×0.2)×1 / (2×1)=0.3
[0110] For further example, if A'=Li is replaced by Sr, the chemical formula is Sr a La b NiO4, at this time U=2, V=3, a+b=2, the specific range needs to be determined according to the limited range of a; c=1, first calculate the formula 0≤a≤1 / 2 (V-U-1) Calculate the value range of a:
[0111] 0≤a≤1 / 2 (3-2-1)
[0112] That is, 0≤a≤1.
[0113] Take a = 0.2, then the chemical formula of the functional material is Sr 0.2 Pr 1.8 The proportion of mixed valence ions in NiO4 and Ni(M) M w :C M w+1 =(1-(VU)×a):(n-1+(VU)×a) is:
[0114] C Ni 2+ :C Ni3+ =(1-(3-2)×0.2):(1-1+(3-2)×0.2)=0.8:0.2
[0115] Ni element multivalent ion mixed valence state (V hybrid )for:
[0116] V hybrid =W+1+(V×aU×a-1) / n=2+1+(3×0.2-2×0.2-1) / 1=2.2
[0117] The theoretical electrochemically controllable maximum oxygen removal / intercalation content in the functional material lattice is:
[0118] O intercal. =(1-V×a+U×a)×c / (2×n)=(1-3×0.2+2×0.2)×1 / (2×1)=0.4
[0119] Similarly, if a=0.5, the chemical formula of the functional material is Sr 0.5 Pr 1.5 NiO4, C Ni 2+ :C Ni 3+ =0.5:0.5, V hybrid =2.5,O intercal. =0.25; if a=1, the chemical formula of the functional material is SrPrNiO4, and the ratio of mixed valence ions in Ni(M) is C Ni 2+ :C Ni 3+ =0:1,V hybrid =3,O intercal. =0, at this time, SrLaNiO4 theoretically cannot absorb oxygen components from the outside and embed them into the lattice, which also has limited effect on inhibiting the oxidation precipitation of lattice oxygen on the surface interface of high-voltage lithium-rich manganese-based positive electrode materials; therefore, the type and content design of A' element has a greater influence on whether the functional material can electrochemically remove / embed oxygen.
[0120] For example, when n=3, a is still a=0.2 because it is not affected by n. At this time, the chemical formula of the functional material is Sr 0.2 Pr 3.8 Ni3O 10 , U = 2, V = 3, b = 3.8, c = 3, d + e = 10; the proportion of mixed valence ions in Ni (M) is C M w :C M w+1 =(1-(VU)×a):(n-1+(VU)×a) is:
[0121] C Ni 2+ :C Ni 3+ =(1-(3-2)×0.2):(3-1+(3-2)×0.2)=0.8:2.2
[0122] Ni element multivalent ion mixed valence state (V hybrid )for:
[0123] V hybrid =W+1+(V×aU×a-1) / n=2+1+(3×0.2-2×0.2-1) / 3=2.73
[0124] Functional Materials Sr 0.2 Pr 3.8 Ni3O 10 The theoretical electrochemically controllable maximum oxygen removal / intercalation content in the lattice is:
[0125] O intercal. =(1-V×a+U×a)×c / (2×n)=(1-3×0.2+2×0.2)×3 / (2×3)=0.4
[0126] Similarly, if n=50, the chemical formula of the functional material is Sr 0.2 Pr 50.8 Ni 50 O 151 , the proportion of mixed valence ions in Ni(M) is C Ni 2+ :C Ni 3+ =0.8:49.2,V hybrid =2.98,O intercal. =0.4;
[0127] If n=100, the chemical formula of the functional material is Sr 0.2 Pr 100.8 Ni 101 O 301 , the proportion of mixed valence ions in Ni(M) is C Ni 2+ :C Ni 3+ =0.8:99.2,V hybrid =2.99,O intercal. =0.4.
[0128] The functional material provided by the present invention has electronic conductivity, electrochemically controllable oxygen ion extraction / insertion and lithium ion electrochemical activity.
[0129] In the present invention, in the synthetic raw materials of the functional material, the metal element medium can be oxides, carbonates, acetates, oxalates or sulfates, etc.; the non-metal element medium can be halides, oxides or simple elements, etc.
[0130] Preferably, the metal element medium may be an oxide, and the non-metal element medium may be a halide or a single element.
[0131] The functional material is obtained by high-temperature sintering according to the stoichiometric ratio required by the calculated formula. The sintering temperature is 600-1200°C, which can be 600, 700, 800, 900, 1000, 1100, 1200, or any value between 600 and 1200°C, and is preferably any value between 800 and 1200°C. The sintering time is 2 to 20 hours, which can be 2, 4, 6, 12, 15, 18, 20, or any value between 2 and 20 hours, and is preferably any value between 6 and 12 hours.
[0132] When it comes to easily oxidized elements such as sulfur (S) and iodine (I), the oxygen partial pressure needs to be controlled during sintering, and the oxygen content is controlled below 2% (Vol.). Otherwise, the sintering atmosphere is air.
[0133] The functional material obtained by sintering is first crushed by a high-energy vibration mill, and the particle D50 is controlled at 6-9um, and then further ground by a sand mill to a particle size of 20-200nm. max ≤1um nanoparticle slurry, the slurry solvent can be an oil system such as N-methylpyrrolidone (NMP), tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) or a deionized water system.
[0134] Preferably, D50 is controlled to be 20-100 nm, and the slurry solvent is N-methylpyrrolidone (NMP).
[0135] The prepared functional materials have metallic lithium as the negative electrode (vs.Li + / Li) is charged and discharged to satisfy the presence of an oxidation characteristic peak above 4.40V on the voltage-capacity differential curve dQ / dV or the cyclic voltammetry curve; a battery is formed in an alkaline aqueous solution with a reversible hydrogen electrode (RHE) as a reference electrode, and there is a redox characteristic peak in the voltage-capacity differential curve dQ / dV or the cyclic voltammetry curve within the range of 1.2-2.0V.
[0136] The prepared functional materials were assembled into a battery with metallic lithium as the negative electrode. When charged to above 4.0V, the Raman spectrum showed a peak at 174cm -1 With 380cm -1 The peak intensity at the position is significantly weakened or eliminated.
[0137] The prepared functional materials were assembled into batteries with metallic lithium as the negative electrode, and cyclic voltammetry tests in the range of 0.001V-3.0V showed the existence of lithium extraction / insertion redox peaks.
[0138] The prepared functional materials were assembled into a battery with metallic lithium as the negative electrode. The lithium ion diffusion coefficient measured by variable scan rate cyclic voltammetry was higher than 10 -13 cm 2 / s.
[0139] After the functional material was pressed into a powder cake with a diameter of 13 mm under a stress of 10 MPa, the electronic conductivity of the powder cake obtained by four-probe testing was higher than 10 mS / cm.
[0140] In the present invention, the surface-modified lithium-manganese-based positive electrode material comprises a lithium-rich manganese-based positive electrode material core and a functional material layer coated on the surface of the lithium-rich manganese-based positive electrode material core.
[0141] The present invention has no special restrictions on the type of the lithium-rich manganese-based positive electrode material core, and any lithium-rich manganese-based positive electrode material known to those skilled in the art can be used. Preferably, the core of the lithium-rich manganese-based positive electrode material has a general chemical formula of Li 1+x Mn y Ni z Co m O2, where 1+x+y+z+m=2, 0≤x≤2, 0<y≤1, 0≤z, m≤1.
[0142] The functional material surface and interface modified lithium manganese-based positive electrode material provided by the present invention realizes controllable reversible electrochemical deintercalation / embedding of oxygen between the coating material and the lithium manganese-rich positive electrode material at different potentials, thereby reducing oxygen loss and ensuring reversible utilization of active oxygen, while avoiding the formation of oxygen gas from escaping to the interface and reacting with the electrolyte to produce side reactions, thereby achieving high temperature and high voltage cycle stability and thermal stability of the material.
[0143] In the present invention, the method for preparing the lithium-rich manganese-based positive electrode material comprises the following steps:
[0144] S1: Mix the lithium-rich manganese-based precursor with the lithium source, and sinter once to obtain a lithium-rich manganese-based positive electrode material; wherein, the present invention has no special restrictions on the mixing method, and the raw material mixing method known to those skilled in the art can be used. In the present invention, ball milling is preferably used. The high-temperature sintering temperature is 600-900°C, which can be 600, 700, 800, 900, or any value between 600 and 900°C, and the sintering time is 2-10h, which can be 2, 3, 4, 5, 6, 7, 8, 9, 10, or any value between 2 and 10h;
[0145] In some preferred embodiments of the present invention, the lithium-rich manganese-based positive electrode material is prepared by uniformly mixing a precursor with an appropriate amount of lithium source by ball milling, and subjected to a three-stage sintering temperature system of 250-400°C low temperature for 2-4 hours, 600-700°C medium temperature for 10-15 hours and 800-900°C high temperature for 2-10 hours.
[0146] S2: Mix the nanoparticle slurry of the functional material with the lithium-rich manganese-based positive electrode material and dry it to obtain a powder; wherein, the present invention has no special restrictions on the preparation method of the nanoparticle slurry of the functional material, and the preparation method of the slurry known to those skilled in the art can be used. In the present invention, the slurry is preferably obtained by sand milling. In the present invention, the mass proportion of the coated nano-functional material in the powder is 0.1wt.% to 5.0wt.%, which can be 0.1wt.%, 0.3wt.%, 0.5wt.%, 0.7wt.%, 1wt.%, 1.5wt.%, 2wt.%, 2.5wt.%, 3wt.%, 3.5wt.%, 4wt.%, 4.5wt.%, 5wt.%, or any value between 0.1wt.% and 5.0wt.%, preferably any value between 0.5wt.% and 2.0wt.%.
[0147] S3: The powder obtained in S2 is subjected to high-temperature secondary sintering to obtain the surface-modified lithium-rich manganese-based positive electrode material, wherein the temperature of the high-temperature secondary sintering is 350°C to 1000°C, which can be 350, 400, 500, 600, 700, 800, 900, 1000, or any value between 350°C and 1000°C, preferably any value between 550°C and 800°C. The time is 2 to 8 hours, which can be 2, 3, 4, 5, 6, 7, 8, or any value between 2 and 8 hours, preferably any value between 2 and 4 hours. The atmosphere of the high-temperature secondary sintering is preferably an air atmosphere condition.
[0148] The surface-modified lithium-rich manganese-based cathode material was assembled into a battery with lithium metal as the negative electrode. The first cycle was charged and discharged in the range of 2.0-4.8V. X-ray photoelectron spectroscopy (XPS) was performed on the surface of the cathode O, F and P. The O1s 531.2eV ROLi organic peak, F1s 685.0eV LiF peak and P2p 136.4eV Li x PO y F z The peak intensity decreased significantly compared to the unmodified control sample.
[0149] The surface-modified lithium-rich manganese-based positive electrode material was assembled into a battery with metallic lithium as the negative electrode. During the first cycle of charge and discharge in the range of 2.0-4.8V, the oxygen content detected by differential electrochemical mass spectrometry (DEMS) was less than 100umol / mg.
[0150] In the present invention, TOF-SIMS analysis is performed on the lithium-rich manganese-based positive electrode material modified at the surface interface of the above functional material, and a uniform coating is formed within 50 nm of the surface layer of the lithium-rich manganese-based positive electrode material.
[0151] See also Figure 1 , Figure 1 Schematic diagram of the electrochemical oxygen desorption / intercalation and lithium ion desorption / intercalation transfer between functional materials and lithium-rich manganese-based positive electrode materials during the charging process. Figure 1 When the lithium-rich manganese-based cathode material is charged, lithium ions escape from the layered structure and are transported and diffused from the lithium ion channel to the electrolyte when passing through the coating material; when further charged to above 4.5V, the lattice oxygen of the layered cathode material loses electrons and oxidizes to form O2 and O2 - , O - and oxygen polymer O n- and other substances and escape to the surface interface of the positive electrode material; under the drive of the electric field, the functional coating material absorbs and embeds the oxygen component into the tetrahedral lattice formed by the adjacent R' or R", and at the same time, the oxidation and valence of the transition metal lithium ions are induced, which prevents the oxygen component from further escaping to the surface interface of the positive electrode material and contacting the electrolyte, thereby inhibiting the electrolyte from being oxidized and decomposed by the oxygen component; in the discharge process, on the contrary, under the drive of the electric field, the functional material releases the oxygen absorbed by the functional material, so that the oxygen can participate in the reduction reaction of the positive electrode; the above process realizes the reversible utilization of the lattice oxygen of the positive electrode material under high voltage, inhibits the precipitation of oxygen and ensures the promotion effect of oxygen activity on the high capacity characteristics of the material.
[0152] The present invention also provides a lithium ion secondary battery, comprising a positive electrode plate, a negative electrode plate, a separator and an electrolyte. The positive electrode plate comprises the above-mentioned surface-interface modified lithium-rich manganese-based positive electrode material.
[0153] The positive electrode sheet is prepared by transfer coating, extrusion coating or gravure coating. For example, the positive electrode active material, binder, conductive agent and organic solvent are first mixed in a predetermined ratio, and the organic solvent can be N-methylpyrrolidone (NMP), and the mixed material is stirred to a uniform system to obtain a positive electrode slurry; then the positive electrode slurry is coated on the positive electrode collector, and after drying, rolling and other processes, the positive electrode sheet is obtained.
[0154] The negative electrode sheet is prepared by transfer coating, extrusion coating or gravure coating. For example, the negative electrode active material, binder, conductive agent and solvent are first mixed in a predetermined ratio, and the organic solvent can be deionized water, and the mixed material is stirred to a uniform system to obtain a negative electrode slurry; then the negative electrode slurry is coated on the negative electrode collector, and after drying, rolling and other processes, the negative electrode sheet is obtained.
[0155] The electrolyte includes lithium salt, additives and solvents, which plays the role of transferring ions between the positive and negative electrodes;
[0156] As some examples, the solvent in the electrolyte is a non-aqueous organic solvent, such as one or more of ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate (PC), fluoropropylene carbonate (FPC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB) and ethyl butyrate (EB), preferably two or more.
[0157] More preferably, the solvent may be selected from two or more of ethylene carbonate (EC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dimethyl carbonate (DMC).
[0158] As some examples, the lithium salt in the electrolyte uses a lithium compound with a high degree of ionization, such as lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluorosulfonyl)imide (LiTFSI).
[0159] Preferably, the lithium salt may be lithium hexafluorophosphate (LiPF6) combined with a small amount of any one or more other lithium salts.
[0160] The function of the additives in the electrolyte is to form a stable solid electrolyte layer at the interface of the positive and negative electrodes, reducing the continuous side reactions between the electrodes and the electrolyte at high or low pressure. The additives include salts, solid organic powders and liquid organic matter.
[0161] As some examples, solid organic powder additives in the electrolyte include vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), methylene disulfonate (MMDS), 1,3-propane sultone (1,3-PS), 1-propylene-1,3-sultone (PST) and diethyl sulfate (DTD); salts include lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiC2BF2O4), lithium difluorophosphate (LiPO2F2), lithium tetrafluoroborate (LiBF4) and lithium bis(oxalatodifluorophosphate) (LiC4O8F2P); liquid organic matter includes bis(2,2,2-trifluoroethyl) carbonate (TFEC), triethyl borate (TEB), trimethoxyboroxine (TMEB), diethyl bis(fluorocarbonate) (DFDEC).
[0162] Preferably, the solid organic additive may be two or more of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), methylene methanedisulfonate (MMDS), 1,3-propane sultone (1,3-PS), 1-propylene-1,3-sultone (PST) and diethylene sulfate (DTD).
[0163] Further preferably, the content of the solid organic additive is 0.1wt.% to 4wt.%, and can be 0.1wt.%, 0.3wt.%, 0.5wt.%, 1wt.%, 1.5wt.%, 2wt.%, 2.5wt.%, 3wt.%, 3.5wt.%, 4wt.%, or any value between 0.1wt.% and 4wt.%.
[0164] Preferably, the lithium salt additive may be, but is not limited to, one or more of lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiC2BF2O4), lithium difluorophosphate (LiPO2F2), and lithium bis(oxalatodifluorophosphate) (LiC4O8F2P).
[0165] Further preferably, the content of the lithium salt additive is 0.1wt.% to 1wt.%, and can be 0.1wt.%, 0.2wt.%, 0.3wt.%, 0.4wt.%, 0.5wt.%, 0.6wt.%, 0.7wt.%, 0.8wt.%, 0.9wt.%, 1wt.%, or any value between 0.1wt.% and 1wt.%.
[0166] The lithium-ion secondary battery of the embodiment of the present invention has no particular limitation on the separator, and any known separator may be used, including PP film, PE film, alumina coating separator, polymer coating separator and solid electrolyte coating separator.
[0167] In order to further understand the present invention, the surface and interface modified lithium-manganese-rich positive electrode material and lithium-ion secondary battery provided by the present invention are described below in conjunction with the embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0168] The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0169] Example 1
[0170] The preparation method of the surface-modified lithium-rich manganese-based positive electrode material provided in this embodiment comprises the following steps:
[0171] Lithium carbonate and nickel-cobalt-manganese precursor Ni 0.16 Co 0.16 Mn 0.68 The mixed material was placed in a box furnace, heated to 350°C at a heating rate of 5°C / min in an air atmosphere, kept warm for 2 hours, then heated to 600°C at a heating rate of 5°C / min and kept warm for 10 hours, and then heated to 850°C at a heating rate of 5°C / min and kept warm for 8 hours. After cooling, the lithium-rich manganese-based positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2;
[0172] The praseodymium oxide and the copper oxide in a stoichiometric ratio are mixed uniformly, the mixture is placed in a muffle furnace, the temperature is increased to 700°C at a heating rate of 5°C / min in an air atmosphere, the temperature is kept for 24 hours, and the Pr2CuO4 functional material is obtained after cooling;
[0173] The Pr2CuO4 functional material is placed in a high-energy vibration mill to crush the particles to a particle size of about D50 = 6um, and then input into a sand mill for grinding, NMP solvent system, after grinding for 24-36 hours, the particle size D50 is controlled to be 50-200nm, and the solid content of the particles is controlled to be 10-30%, preferably the particle size is controlled to be 50nm, and the solid content is 20%;
[0174] The functional material slurry and the lithium-rich manganese-based positive electrode material were weighed according to a coating amount of 0.3 wt.%, fully dispersed in a planetary mixer for 2 h, and then dried to obtain the material;
[0175] The mixed material was placed in a muffle furnace, heated to 600°C at a heating rate of 5°C / min in an air atmosphere, kept warm for 2 hours, and after cooling, a lithium-rich manganese-based positive electrode material coated with Pr2CuO4 functional material was obtained.
[0176] Example 2
[0177] In this embodiment, the sintering temperature of the Pr2CuO4 functional material in Embodiment 1 is changed to 800°C, and the other conditions remain unchanged.
[0178] Example 3
[0179] In this embodiment, the sintering temperature of the Pr2CuO4 functional material in Embodiment 1 is changed to 900°C, and the other conditions remain unchanged.
[0180] Example 4
[0181] In this embodiment, the sintering temperature of the Pr2CuO4 functional material in Embodiment 1 is changed to 1000°C, and the other conditions remain unchanged.
[0182] Example 5
[0183] In this example, the coating amount of 0.3wt.% in Example 4 is changed to 0.5wt.%, and the other conditions remain unchanged.
[0184] Example 6
[0185] In this example, the coating amount of 0.3 wt.% in Example 4 is changed to 1.0 wt.%, and the other conditions remain unchanged.
[0186] Example 7
[0187] In this embodiment, the Pr2CuO4 functional material in Example 6 is changed to Pr2NiO4 functional material. The raw materials are praseodymium oxide and nickel oxide, and the other conditions remain unchanged.
[0188] Example 8
[0189] In this embodiment, the Pr2CuO4 functional material in Embodiment 6 is changed to Pr2FeO4 functional material. The raw materials are praseodymium oxide and ferrous oxide, and the other conditions remain unchanged.
[0190] Example 9
[0191] In this embodiment, the Pr2CuO4 functional material in Embodiment 6 is changed to Pr2CoO4 functional material. The raw materials are praseodymium oxide and cobalt oxide, and the other conditions remain unchanged.
[0192] Example 10
[0193] In this embodiment, the Pr2CuO4 functional material in Embodiment 6 is changed to Pr2MnO4 functional material. The raw materials are praseodymium oxide and manganese oxide, and the other conditions remain unchanged.
[0194] Embodiment 11
[0195] In this embodiment, the Pr2CuO4 functional material in Example 6 is changed to Sm2NiO4 functional material. The raw materials are samarium oxide and nickel oxide, and the other conditions remain unchanged.
[0196] Example 12
[0197] In this embodiment, the Pr2CuO4 functional material in Embodiment 6 is changed to Nd2NiO4 functional material. The raw materials are nickel oxide and neodymium oxide, and the other conditions remain unchanged.
[0198] Embodiment 13
[0199] In this embodiment, the Pr2CuO4 functional material in Example 6 is changed to Sc2NiO4 functional material. The raw materials are scandium oxide and nickel oxide, and the other conditions remain unchanged.
[0200] Embodiment 14
[0201] In this embodiment, the Pr2CuO4 functional material in Embodiment 6 is changed to Y2NiO4 functional material. The raw materials are yttrium oxide and nickel oxide, and the other conditions remain unchanged.
[0202] Embodiment 15
[0203] In this embodiment, the Pr2CuO4 functional material in Example 6 is changed to Li 0.2 Pr 1.8 CuO4 functional material, the raw materials are lithium carbonate, oxide spectrum and copper oxide, and the other conditions remain unchanged.
[0204] Example 16
[0205] In this embodiment, the Pr2CuO4 functional material in Example 6 is changed to Li 0.5 Pr 1.5 CuO4 functional material, the raw materials are lithium carbonate, oxide spectrum and copper oxide, and the other conditions remain unchanged.
[0206] Embodiment 17
[0207] In this embodiment, the Pr2CuO4 functional material in Example 6 is changed to Sr 0.5 Pr 1.5 CuO4 functional material, the raw materials are strontium carbonate, copper oxide and copper oxide, and the other conditions remain unchanged.
[0208] Embodiment 18
[0209] In this embodiment, the Pr2CuO4 functional material in Embodiment 6 is changed to SrPrCuO4 functional material. The raw materials are strontium carbonate, copper oxide and copper oxide, and the other conditions remain unchanged.
[0210] Embodiment 19
[0211] In this embodiment, the Pr2CuO4 functional material in Example 6 is changed to Li 0.2 Pr 1.8 Cu 0.5 Fe 0.5 O4 functional material, the raw materials are lithium carbonate, oxide spectrum, copper oxide and ferrous oxide, and the other conditions remain unchanged.
[0212] Embodiment 20
[0213] In this embodiment, the Pr2CuO4 functional material in Example 6 is changed to Li 0.2 Pr 1.8 Cu 0.5 Mn 0.5 O4 functional material, the raw materials are lithium carbonate, oxide spectrum, copper oxide and manganese oxide, and the other conditions remain unchanged.
[0214] Embodiment 21
[0215] In this embodiment, the Pr2CuO4 functional material in Example 6 is changed to Li 0.2 Pr 1.8 Cu 0.33 Fe 0.33 -Mn 0.34 O4 functional material, the raw materials are lithium carbonate, oxide spectrum, copper oxide, ferrous oxide and manganese oxide, and the other conditions remain unchanged.
[0216] Embodiment 22
[0217] In this embodiment, the Pr2CuO4 functional material in Example 6 is changed to Li 0.2 Pr 1.6 Ce 0.2 CuO4 functional material, the raw materials are lithium carbonate, oxide spectrum, cerium oxide and copper oxide, and the other conditions remain unchanged.
[0218] Embodiment 23
[0219] In this embodiment, the Pr2CuO4 functional material in Example 6 is changed to Pr3Ni2O7 functional material. The raw materials are oxidation spectrum and nickel oxide, and the other conditions remain unchanged.
[0220] Embodiment 24
[0221] In this embodiment, the Pr2CuO4 functional material in Example 6 is changed to Pr4Ni3O 10 Functional materials, the raw materials are oxide spectrum and nickel oxide, and the other conditions remain unchanged.
[0222] Comparative Example 1
[0223] In this comparative example, the Pr2CuO4 functional material in Example 6 is changed to Al2O3, and the other conditions remain unchanged.
[0224] Comparative Example 2
[0225] In this comparative example, the Pr2CuO4 functional material in Example 6 is changed to Y2O3, and the other conditions remain unchanged.
[0226] Comparative Example 3
[0227] In this comparative example, the Pr2CuO4 functional material in Example 6 is changed to TiO2, and the other conditions remain unchanged.
[0228] Comparative Example 4
[0229] In this comparative example, the Pr2CuO4 functional material in Example 6 is changed to ZrO2, and the other conditions remain unchanged.
[0230] Comparative Example 5
[0231] In this comparative example, the Pr2CuO4 functional material in Example 6 is changed to lithium aluminum titanium phosphate (LATP), and the other conditions remain unchanged.
[0232] Characterization analysis
[0233] Scanning electron microscopy (SEM): The surface morphology was characterized using a Hitachi S4800 field emission electron microscope (FE-SEM, S4800).
[0234] X-ray photoelectron spectroscopy (XPS) test: The XPS test uses the ESCALAB 250Xi photoelectron spectrometer of Thermo Fisher Scientific, and the light source is monochromatic Al Kα X-ray. The sample preparation process is as follows: the cycled battery is disassembled in the glove box, the positive electrode is taken out and washed three times with DMC to remove the residual electrolyte, and then placed in the glove box transition chamber and evacuated for 2 hours to remove the solvent. The sample is transferred to the XPS instrument using the sample transfer box made by Thermo Fisher Scientific to avoid contact between the sample and the air. The data obtained from the test is fitted and quantitatively analyzed using Avantage software. The energy correction of the spectral data is to correct the peak energy value corresponding to the CC bond (conductive additive) in the C1s spectrum to 284.8eV.
[0235] X-ray diffraction (XRD): The phase characterization of the samples was carried out using an X-ray diffractometer from Bruker, Germany. The model of the equipment was D8 Advance diffractometer. The radiation source used was Cu Kα. The scanning angle range was 10-80° and the scanning speed was 0.05° / min.
[0236] Time-of-flight secondary ion mass spectrometer (TOF-SIMS): Japan PHI nano TOFⅡ, 0.25-2keV O 2+ Oxygen cluster ion source, 0.25-2keV Cs +Cesium ion source and 2.5-20keV Ar + An argon cluster ion source was used to collect surface mass spectrometry, depth profiling, and imaging data of the samples.
[0237] Synchronous thermal analyzer (DSC): The instrument model used is German Netzsch STA 499C. Before the test, the sample powder charged to 4.8V was scraped from the current collector, and 2mg of the sample and 1mL of the electrolyte were added to a stainless steel high-pressure sealed crucible for testing. The heating rate was 5℃ / min, and the test temperature range was 50-600℃.
[0238] Electronic conductivity: The electronic conductivity of the material is tested using a four-probe resistance analyzer RTS-5 (Guangzhou Four-probe). 0.1g of powder is placed in a 15mm round wafer sample making machine, and after applying 12kN stress to make a wafer, it is placed in a four-probe instrument to measure the electronic conductivity.
[0239] Differential electrochemical mass spectrometer (DEMS): An in-situ differential electrochemical mass spectrometer built using Hiden HRP-20 from the UK was used to detect the oxygen release rate in real time.
[0240] Raman spectroscopy: The equipment used is ThermoFisher DXR laser microscope Raman spectrometer, laser wavelength 523nm, measurement range 0~1600cm -1 .
[0241] Determination of oxygen content: The absolute oxygen excess stoichiometry (σ) was determined by reverse dichromate titration at 25°C. The method is based on treating the sample with a known excess of Fe(II) and subsequent titration with a standard potassium dichromate (K2Cr2O7) solution. Chemically pure Mohr's salt (Fe(NH4)2(SO4)2·6H2O) was used as the source of Fe(II) and 1:4 hydrochloric acid (HCl, chemically pure) was used as the solvent for the complex oxides analyzed. The potassium dichromate in the working solution was prepared from high-purity K2Cr2O7. The functional material powder was pre-purged with argon to prevent the release of oxygen into the atmosphere during sample dissolution. The powder was dissolved with HCl in an argon atmosphere together with Mohr's salt and titrated potentiometrically with 0.1N standard potassium dichromate. The endpoint was fixed potentiometrically using an ATP-02 automatic titrator. The oxygen content in the functional material was calculated using the following formula:
[0242]
[0243] Battery preparation:
[0244] Preparation of pole pieces: Place the lithium-manganese-rich positive electrode material samples, acetylene black and polyvinylidene fluoride in a 60°C vacuum drying oven and dry for 12 hours. Take the dried material, add it to N-methylpyrrolidone as a solvent in a mass ratio of 8:1:1 and mix thoroughly. Apply the evenly dispersed slurry evenly on the aluminum foil current collector in a dew point room. Place the pole piece in a 55°C oven for 5 hours until the NMP is completely volatilized, then cut into discs with a diameter of 12 mm, weigh them, and place them in a 120°C vacuum oven for 6 hours to completely remove the water and solvent in the pole piece. Finally, take out the dried pole piece and transfer it to a glove box. The surface density of the prepared pole piece active material is 3-5 mg / cm 2 about.
[0245] Battery assembly: The battery was assembled in a glove box filled with argon. The button battery shell model used was R2032 (made of 304 stainless steel), the electrolyte was the electrolyte FEC:EMC=2:8 (Vol.%) prepared in the embodiments of the present invention and the comparative example, 1.2 mol / L LiPF6; the diaphragm was a 25 um polypropylene diaphragm, and the negative electrode was a metal lithium sheet with a diameter of 16.3 mm and a thickness of 500 um.
[0246] Battery Test:
[0247] After the battery is assembled, it is placed for more than 2 hours to allow the electrolyte to fully penetrate the inside of the electrode. Then the charge and discharge test is carried out on the Land CT 3002A (Wuhan Blue Electric) charge and discharge tester, with a charge and discharge current density of 25mA / g, a voltage range of 2.0-4.8V, and a standard specific capacity C0 (mAh / g) after 3 cycles.
[0248] Cycle test: 25℃ / 45℃, 1.0C / 1.0C, 2.0-4.8V, 1.0C=C0 (mAh / g).
[0249] Rate test: 25℃, 0.1C / 0.1C, 0.2C / 0.2C, 0.3C / 0.3C, 0.5C / 0.5C, 1.0C / 1.0C, 2.0C / 2.0C, 5.0C / 5.0C, 2.0-4.8V, 1.0C=C0(mAh / g).
[0250] EIS AC impedance test: Zahner electrochemical workstation (Zahner, Germany) was used with a test frequency of 5 MHz-50 mHz and a voltage amplitude of 10 mV.
[0251] Cyclic voltammetry test: The test was conducted using a CHI604E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.), with scanning performed at room temperature and a scan rate of 0.1-0.6 mV / s; the redox peak potential was obtained through cyclic voltammetry; and the lithium ion diffusion coefficient was obtained through variable scan rate cyclic voltammetry.
[0252] The physical properties of the interface-modified lithium-rich manganese-based positive electrode materials in the above-mentioned embodiments and comparative examples are summarized in Table 1.
[0253] Table 1
[0254]
[0255]
[0256] The electrochemical properties of the interface-modified lithium-rich manganese-based positive electrode materials of the above-mentioned examples and comparative examples are summarized in Table 2.
[0257] Table 2
[0258]
[0259]
[0260] As can be seen from the above, the present invention proposes a surface-modified lithium-rich manganese-based positive electrode material and a lithium-ion secondary battery, which aims to utilize the functional coating material to remove active oxygen species, such as O from the surface interface of the lithium-rich manganese-based positive electrode material particles under potential drive when charged to a high voltage. 2 、O2 - , O - and oxygen polymer O n- The absorption is embedded in the lattice gap, and active oxygen is released when discharged to a low potential. The lithium-rich manganese-based positive electrode material modified based on functional materials has good electrochemical properties in lithium-ion secondary batteries.
[0261] From the comparative analysis of Example 1 and Example 4, it can be seen that for the coating material with the same theoretically removable / embedded oxygen content in the lattice, the first oxidation peak potential of Example 4 is lower, and the oxygen content monitored by DEMS is lower (60.3mmol / g vs.71.3mmol / g). th The higher the cycle capacity retention rate (75.3% vs. 69.8%), the higher the DSC thermal decomposition temperature (145.5°C vs. 143.2°C).
[0262] By comparing Example 6 with Examples 16 and 18, it is found that for samples without the theoretically removable / intercalable oxygen content in the lattice, the oxygen content monitored by DEMS is very high (46.4 mmol / g vs. 421.4 mmol / g), and the DSC thermal decomposition temperature decreases (146.7°C vs. 140.2°C), and the high-temperature cycle stability at 45°C is also significantly deteriorated (78.1% vs. 71.6%).
[0263] Comparing Examples 1-24 with Comparative Examples 1-5, all of the oxygen contents monitored by DEMS using the technical solutions provided by the present invention are significantly reduced, the cycle stability is improved, and the thermal stability of the highly delithiated lithium-rich manganese-based positive electrode materials is also improved.
[0264] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A surface-modified lithium-rich manganese-based positive electrode material, characterized in that: It comprises a lithium-rich manganese-based positive electrode material core and a functional material layer coated on the surface of the lithium-rich manganese-based positive electrode material core. The chemical formula of the functional material is shown in chemical formula (1): R' a R” b M c A' d A” e Chemical formula (1) In the chemical formula (1), R' is one or more of alkali metal or alkaline earth metal Li, Na, K, Rb, Cs, Mg, Ca, Sr and Ba; R" is one or more of the lanthanide rare earth elements La, Ce, Pr, Nd, Po, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc, and Y; M is one or more of the transition metal elements Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Cd and Ta that can change into multiple valence states; A' is O; A" is one or more of S, Se, Te, F, Cl, Br and I; The valence of the M element in the functional material includes a non-highest valence state of the M element, and / or, in a battery with metallic lithium as a negative electrode, a redox peak exists in a cyclic voltammetry curve in the potential range of 2.0-5.0V; Ions M with a valence of +w in element M W With +(w+1) ion M w+1 The amount ratio of the substance satisfies the relationship of formula 1: C M w : C M w+1 = (1 - (V - U)×a) : (n - 1 + (V - U)×a) (Equation 1) Multivalent ions of element M with mixed valence (V hybrid ) satisfies the relationship in formula 2: V hybrid = W+1+(V×aU×a-1) / n (Formula 2) In formula 1 and formula 2, C M w , C M w+1 M W With M w+1 The proportion of the amount of a substance; U is the valence of the element R'; V is the valence of the element R"; W is the valence of the element M; n is the stoichiometric ratio of the elements in the chemical formula (1); U, V, W and n are all positive integers greater than zero; a is the content of R' element, and its value interval satisfies the relationship of formula 3: 0 ≤ a ≤ 1 / 2 (V -U-1) (Formula 3) In formula 3, a is the content of R' element, U is the valence of R' element; V is the valence of R' element; U and V are positive integers greater than zero; The theoretical electrochemically controllable maximum oxygen removal / intercalation content in the functional material lattice satisfies the relationship of formula 4: O intercal. = (1-V×a+U×a)×c / (2×n) (Formula 4) Where O intercal. is the theoretical electrochemically controllable maximum oxygen removal / embedding content in the functional material lattice, U is the valence of the R' element; V is the valence of the R" element; n is the stoichiometric ratio of the elements in the chemical formula (1), U, V, and n are positive integers greater than zero; a is the R' element content, and its assignment interval satisfies the relationship of formula 3; Assuming that the valences of R', R", M, A' and A" are U, V, W, X and Y respectively, the general chemical formula R' a R” b M c A' d A” e In the equation, a, b, c, d and e satisfy the relationship between equations 5 and 6: a×U+b×V+c×W=d×Y+e×Z (Formula 5) (a+b): c: (d+e)= (n+1): n: (3 n+1) (Formula 6) In Formula 5 and Formula 6, U, V, W, X, Y and n are positive integers greater than zero; a, b, c, d and e are rational real numbers greater than or equal to zero, including decimals.
2. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: When the functional material is assembled into a battery with metal lithium as the negative electrode, when charged to above 4.0V, the Raman spectrum has a peak at 174cm -1 With 380cm -1 The peak intensity at the position is weakened or eliminated.
3. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The functional material is assembled into a battery with metal lithium as the negative electrode for charging and discharging, and an oxidation characteristic peak above 4.40V exists on the voltage capacity differential curve dQ / dV or the cyclic voltammetry curve; Alternatively, after the functional material is used to form a battery in an alkaline aqueous solution with a reversible hydrogen electrode (RHE) as a reference electrode, a redox characteristic peak exists in the voltage capacity differential curve dQ / dV or the cyclic voltammetry curve within the 1.2-2.0V range.
4. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The functional material is assembled into a battery with metallic lithium as the negative electrode for charging and discharging, and the voltage capacity differential curve dQ / dV or the cyclic voltammetry curve has a lithium extraction / insertion redox peak in the range of 0.001V-3.0V; And / or, the functional material is assembled into a battery with metallic lithium as the negative electrode, and the lithium ion diffusion coefficient measured by variable scan rate cyclic voltammetry is higher than 10 -13 cm 2 / s.
5. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The functional material is pressed into a powder cake with a diameter of 13 mm by a stress of 10 MPa. The electronic conductivity of the powder cake obtained by a four-probe test is higher than 10 mS / cm.
6. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The surface-modified lithium-rich manganese-based positive electrode material was assembled into a battery with lithium metal as the negative electrode. The battery was charged and discharged in the range of 2.0-4.8V in the first cycle. X-ray photoelectron spectroscopy (XPS) was performed on the surface of the positive electrode sheet. The O1s 531.2eV ROLi organic peak, the F1s 685.0eV LiF peak and the P2p 136.4eV Li x PO y F z The peak intensity is lower than the peak intensity of the unmodified lithium-rich manganese-based cathode material at the surface interface; And / or, the surface-modified lithium-rich manganese-based positive electrode material is assembled into a battery with metallic lithium as the negative electrode, and the oxygen content detected by differential electrochemical mass spectrometry (DEMS) is less than 100umol / mg during the first cycle of charging and discharging in the range of 2.0-4.8V.
7. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The core chemical formula of the lithium-rich manganese-based positive electrode material is Li 1+x Mn y Ni z Co m O2, where 1+x+y+z+m=2, 0≤x≤2, 0<y≤1, 0≤z, m≤1.
8. A method for preparing a lithium-rich manganese-based positive electrode material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: mixing a lithium-rich manganese-based precursor with a lithium source, and sintering once to obtain a lithium-rich manganese-based positive electrode material core; S2: mixing the nanoparticle slurry of the functional material with the lithium-rich manganese-based positive electrode material core and drying the mixture to obtain a powder; S3: performing secondary sintering at high temperature on the powder to obtain the surface-interface modified lithium-rich manganese-based positive electrode material.
9. A lithium ion secondary battery, characterized in that: A lithium-rich manganese-based positive electrode material with surface and interface modification comprising any one of claims 1 to 7.
Citation Information
Patent Citations
Modified lithium-rich manganese-based material, preparation method, positive electrode material, positive electrode plate and battery
CN118553892A
Modified lithium-rich manganese-based material, modification method of lithium-rich manganese-based material, secondary battery, and electrical device
WO2024026621A1
Cited By
Lithium-rich manganese-based lithium ion battery, activation method thereof and electric device
CN119994260A
A lithium-rich manganese-based lithium-ion battery, its activation method, and an electric device
CN119994260B
Positive pole piece, preparation method thereof and lithium ion battery
CN120690805A
Surface cation disordered modified lithium-rich manganese-based positive electrode material, preparation method thereof and lithium battery
CN121662792A
A surface cation-disordered modified lithium-rich manganese-based positive electrode material, a preparation method thereof and a lithium battery
CN121662792B